The strategic management of higher education serving students as customers for institutional growth - Kazeroony, Hamid H. (Strategic management collection, 2012)
This book is targeted at the professionals who are interested in reorganizing or restructuring their higher education or postsecondary institutions. It examines the needs of learners in the 21st century, the rise of for-profit higher-education institutions, and the technological innovations impacting postsecondary education. It also provides examples of administrative processes and how to satisfy regulatory agencies' standards to take advantage of a particular marketing niche for attracting students. This book is organized into 13 chapters that address the changing environment of higher education and the administrative structure, challenges, and requirements for successful execution of start-up operations or changing strategies for existing institutions, as well as provide a summary of findings and additional recommendations.